Undercorrection of planovalgus deformity after calcaneal lengthening in patients with cerebral palsy - Cho, Byung Chae; Lee, In Hyeok; Chung, Chin Youb; Sung, Ki Hyuk; Lee, Kyoung Min; Kwon, Soon Sun; Moon, Seung Jun; Kim, Jaeyoung; Lim, Hyunwoo; Park, Moon Seok (Journal of Pediatric Orthopaedics Part B, 2018)
Calcaneal lengthening (CL) is one of the treatment options for planovalgus deformity in patients with cerebral palsy (CP). However, its indication still needs to be clarified according to the functional status of CP. The aim of this study was to investigate the radiographic outcome after CL in patients with CP and to evaluate the risk factors causing undercorrection of planovalgus deformities. We included consecutive patients with CP who underwent CL for planovalgus deformity, were followed for more than 2 years, and had preoperative and postoperative weight-bearing anteroposterior (AP) and lateral foot radiographs. Six radiographic indices were used to assess the radiographic outcome. The patient age, sex, and Gross Motor Function Classification System (GMFCS) level were evaluated as possible risk factors, and we controlled for the interaction of potentially confounding variables using multivariate analysis. A total of 44 (77 feet) patients were included in this study. The mean age of the patients at the time of surgery was 10.5±4.0 years and the mean follow-up was 5.1±2.2 years. Patients with GMFCS III/IV achieved less correction than those with GMFCS I/II in the AP talus-first metatarsal angle (P=0.001), lateral talocalcaneal angle (P=0.028), and the lateral talus-first metatarsal angle (P<0.001). The rate of undercorrection in the GMFCS III/IV group was 1.6 times higher than that in the GMFCS I/II group in the AP talus-first metatarsal angle (odds ratios: 1.6; 95% confidence interval: 1.2-2.0; P<0.001) and 1.6 times higher in the lateral talus-first metatarsal angle (odds ratios: 1.6; 95% confidence interval: 1.3-1.9; P<0.001). In GMFCS I/II patients with CP, we found CL to be an effective procedure for the correction of planovalgus foot deformities. However, in GMFCS III/IV patients with planovalgus deformities, CL appears to be insufficient on the basis of the high rate of undercorrection in these patients. For patients with GMFCS level III/IV, additional or alternative procedures should be considered to correct the deformity and maintain the correction achieved. Level of evidence: Level III, therapeutic study.
Keywords: Adolescent; Adult; Calcaneus; Cerebral Palsy; Child; Child, Preschool; Female; Foot Deformities, Acquired; Humans; Male; Retrospective Studies; Young Adult; calcaneal lengthening; cerebral palsy; planovalgus; undercorrection